FDG PET/CT in Tenosynovial Giant Cell Tumor of the Lumbar Facet Joint. (January 2022) - Zhang, Jian; Li, Yuhan; Zhu, Yanfang; Duan, Ying; Zhu, Yuzhao
Abstract : Abstract: Tenosynovial giant cell tumor rarely affects the facet joints of the spine. We describe FDG PET/CT findings in a case of tenosynovial giant cell tumor arising from the left L2 to L3 facet joint. The tumor caused osteolytic bone destruction of the facet joint and showed intense FDG uptake with SUVmax of 10.4. This case indicates tenosynovial giant cell tumor should be included in the differential diagnosis of abnormal facet joint FDG accumulation.